(untitled) (Linguamática, 2017)
In this paper we propose the use of lexical, syntactic and semantic knowledge for coreference resolution. We conducted several experiments involving different heuristics. As a result of this study, we generated a practical system that solves coreference in Portuguese texts. In addition, it was possible to increase our recall through semantic knowledge provided by Onto.PT.